Spectrophotometric Determination of Clonazepam in Pure and Dosage forms using Charge Transfer Reaction - Hadi, Hind (Iraqi Journal of Pharmaceutical Sciences, 2017)
A rapid, sensitive and without extraction spectrophotometric method for determination of clonazepam (CLO) in pure and pharmaceutical dosage forms has been described. The proposed method was simply depended on charge transfer reaction between reduced CLO (n-donor) and metol (N-methyl-p-aminophenol sulfate) as a chromogenic reagent (Ï€- acceptor). The reduced drug, with zinc and concentrated hydrochloric acid, produced a purple colored soluble charge-transfer complex with metol in the presence of sodium metaperiodate in neutral medium, which has been measured at Î»max 532 nm. All the variables which affected the developed and the stability of the colored product such as concentration of reagent and oxidant, temperature and time of reaction were investigated and optimized. The linearity of the method was observed within a concentration range 5-40 Î¼g ml-1 CLO and with a correlation coefficient not less than 0.998, while the molar absorbitivity and sandell sensitivity were 3.473Ã—103 L.mole-1.cm-1 and 0.0909 Î¼g cm-2 respectively. The present work includes also the usage of the Benesiâ€“Hildebrand equation for the evaluation of the association constant and molar absorptivity of the colored complex .Finally the proposed method was successfully applied for the determination of CLO in tablets.Keywords: Spectrophotometric ; Clonazepam ; Metol ; Charge-transfer reaction.